Youth unemployment as a socio-economic problem of the labor market ("Journal "U". Economy. Management. Finance.", 2025)
The article analyses youth unemployment as a socio economic problem. Its dual nature is demonstrated: macroeconomic causes and social consequences. The key features of the issue are identified, and solutions are proposed — retraining, government employment programmes, startup support, and internships. The necessity of systemic measures to unlock the potential of young people is emphasised.
Keywords: unemployment; youth; labour market; employment; vocational training; job placement